Exchange Rate Pass-through to Prices: VAR Evidence for Albania - Matuka, Adelajda (International Journal of Business, Economics and Management, 2019)
This study estimates exchange rate pass-through to prices in Albania using a Vector Autoregressive model from 2000Q1 to 2017 Q1 following Cholesky decomposition. We perform an Augmented Dickey-Fuller test and Phillips-Pherron test to ensure the stationarity of the variables and we estimate the impulse-response functions and the variance decomposition of import, producer, consumer prices and interest rate to oil price /exchange rate shocks. Impulse-response functions indicate an incomplete pass-through of exchange rate to prices and the highest response is of consumer prices and interest rates. Variance decomposition indicates that the variance of import prices is explained by growth rate, its shocks and oil prices shocks. The variance of producer prices is explained by its own shocks, real GDP rate and interest rate whilst consumer prices are explained by its innovations, GDP rate and exchange rate. In order to confirm our results, we order the interest rate before the exchange rate and the findings do not change from the previous results. We perform diagnostic tests for the presence of autocorrelation and the stability of our model and the results show that we fail to reject the null hypothesis for serial autocorrelation and all the roots lie within the companion matrix. However, there is evidence on non-normality in our VAR residuals, but this does not violate our analysis.